2002
DOI: 10.1021/jp012492n
|View full text |Cite
|
Sign up to set email alerts
|

UV Resonance Raman Characterization of Model Compounds of Tyr244 of Bovine Cytochrome c Oxidase in Its Neutral, Deprotonated Anionic, and Deprotonated Neutral Radical Forms:  Effects of Covalent Binding between Tyrosine and Histidine

Abstract: A model compound of Tyr244-His240 of bovine cytochrome c oxidase was synthesized and examined with UV resonance Raman (UVRR) as well as UV absorption spectroscopy and pH titration. Owing to the covalent linkage between imidazole and phenol, the pK a of phenolic OH and imidazolic NδH groups were lowered by 1.1 and 2.3, respectively. UVRR measurements of ortho-imidazole-bound para-cresol (Im⧫CrOH), its deprotonated anion (Im⧫CrO-), and deprotonated neutral radical (Im⧫CrO•), and their imidazole perdeuterated, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
74
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 46 publications
15
74
0
Order By: Relevance
“…However, three positive bands in the P m -O difference spectrum indicate the presence of a tyrosine radical in P m . The 1,587-cm Ϫ1 band concurs with the CAC stretching vibration observed at 1,587 cm Ϫ1 in the deprotonated neutral radical form of orthoimidazole-bound para-cresol, a model compound for the crosslinked histidine-tyrosine (33). Either of the two positive bands at 1,528 cm Ϫ1 and 1,517 cm Ϫ1 in the P m -O difference spectrum can be assigned to the C-C stretch of the radical form of cross-linked histidine-phenol observed at 1,522 cm Ϫ1 (34).…”
Section: Resultssupporting
confidence: 72%
“…However, three positive bands in the P m -O difference spectrum indicate the presence of a tyrosine radical in P m . The 1,587-cm Ϫ1 band concurs with the CAC stretching vibration observed at 1,587 cm Ϫ1 in the deprotonated neutral radical form of orthoimidazole-bound para-cresol, a model compound for the crosslinked histidine-tyrosine (33). Either of the two positive bands at 1,528 cm Ϫ1 and 1,517 cm Ϫ1 in the P m -O difference spectrum can be assigned to the C-C stretch of the radical form of cross-linked histidine-phenol observed at 1,522 cm Ϫ1 (34).…”
Section: Resultssupporting
confidence: 72%
“…Several studies of histidine-tyrosine model compounds have been reported (25)(26)(27)(28)(29)(30)(31)(32) supporting stabilization of a neutral tyrosine radical. However, the ligated copper, not included in these models, also is likely to affect the properties of the histidine-tyrosine dimer, which is the actual ligand of Cu B (33), and might increase its acidity and stabilize the neutral radical beyond that shown for the model compounds.…”
Section: Discussionmentioning
confidence: 96%
“…Nyquist and coworkers attributed bands at 1528 and 1517 cm −1 to the C-C ring stretching frequencies of the tyrosine-histidine radical in R. sphaeroides cytochrome c oxidase 16. However, previous Raman spectroscopic studies of ortho -imidazole-bound para -cresol-based model compounds, with and without copper, have attributed bands around 1530 – 1533 cm −1 to the CO stretching vibration 35, 38, 47. The good agreement between the vibrational assignments presented here for the ligand and the Cu-complex and those observed in the spectra of the P M intermediate of cytochrome c oxidase from different species provides further support for the presence of a tyrosyl radical in the P M intermediate of cytochrome oxidase.…”
Section: Discussionmentioning
confidence: 99%